Stimulation of tentacle and bud formation by the neuropeptide head activator in Hydra magnipapillata - Hobmayer, Bert; Holstein, Thomas W.; Davidson, Charles N. (Developmental biology, 1997)
Stimulation of epithelial cell cycling by the neuropeptide head activator was analyzed inHydra magnipapillataand compared with the action of head activator on bud formation and tentacle formation during head regeneration. The results obtained indicate that head activator treatment stimulates epithelial cell division and induces the formation of more tentacle-specific epithelial cells. The number of additional epithelial cells which undergo mitosis during head activator treatment accounts for the increased number of epithelial cells present in the regenerated tentacles. Therefore, the head activator stimulation of tentacle formation can be explained by the mitogenic action of head activator on tentacle cell precursors. To analyze stimulation of bud formation by head activator, polyps of different developmental age were tested under conditions of long-term treatment, and effects on bud formation were compared with effects on epithelial cell proliferation. Head activator treatment strongly stimulated bud formation, but had no detectable effect on epithelial cell numbers. Bud formation occurs at smaller polyp size as a result of head activator treatment, indicating that head activator significantly interferes with the patterning system in hydra.
Gesehen am 26.01.2017